Mafic rocks with back-arc E-MORB affinity from the Chotanagpur Granite Gneiss Complex of India: relicts of a Proterozoic Ophiolite suite. (18th September 2021) - Ahmad, Mansoor; Paul, Abdul Qayoom; Negi, Priyanka; Akhtar, Salim; Gogoi, Bibhuti; Saikia, Ashima
Abstract: The Proterozoic Chotanagpur Granite Gneiss Complex (CGGC) at the northern boundary of the Central Indian Tectonic Zone (CITZ) of the eastern Indian shield preserves relics of fossilized oceanic back-arc crust. We describe the field, petrographical and geochemical characteristics of the mafic rocks comprising pillow basalts and dolerites from the Bathani area of the northern fringe of the CGGC, eastern India. The basalts consist of plagioclase feldspar, hornblende, opaque minerals (Fe–Ti oxide) and chlorite, and the dolerite consists of plagioclase, hornblende and opaque minerals. Our data indicate that the Bathani mafic rocks have tholeiitic to transitional composition and are overprinted by greenschist facies metamorphic conditions; however, REE and fluid immobile elements preserve their primary geochemical signatures. The (La/Sm)N ratios (1.38–2.15) and chondrite-normalized REE patterns point to an enriched mid-ocean ridge basalt (E-MORB) mantle source. Geochemical characteristics indicate a mixed signature of MORB and arc tholeiite with enrichment of Ba, Th, Eu and Sr, similar to that of back-arc supra-subduction zone ophiolites. These mafic rocks are the product of MORB-like magma derived from a depleted mantle corresponding to < 2% partial melting of spinel lherzolite, enriched by subduction-induced slab metasomatism and melting. The Bathani mafic rocks are representative of the upper part of a supra-subduction zone columnar ophiolite section, which was emplaced onto the present-day northern margin of the CGGC during suturing of the northern and southern Indian block at c.  1.9 Ga during the Nuna amalgamation.